Dream Interpretation: Case Study - Pandey, Neerja (Journal of Neonatal Surgery, 2025)
This single-case qualitative study explores the psychotherapeutic application of dream interpretation in addressing recurrent nightmares experienced by young adult female client during transitional phase of her life. As the client prepared for marriage and relocation abroad, she sought psychological clarity and resolution. The frequency and intensity of her nightmares had been increasing which were later understood to reflect unprocessed emotional conflicts. The structured dream analysis and therapeutic session facilitated access to latent emotions, specifically sadness, fear, and betrayal, rooted in early familial relationships. The process illuminated unresolved familial conflicts—specifically, longstanding resentment toward her mother and a perception of betrayal by her younger sister—which had subconsciously shaped her emotional landscape and interpersonal relationships. The intervention facilitated emotional catharsis, leading to cognitive and emotional reframing. Ultimately, the client gained insight into how repressed emotions had influenced her life, enabling her to move forward with greater emotional clarity and resilience. This case highlights the value of symbolic exploration in dream content as a transformative tool for intrapsychic integration and emotional healing.